Experimental observation of hysteresis in a coherent metal-hydride phase transition. (16th November 2017) - Huang, Wen; Pálsson, Gunnar K; Brischetto, Martin; Droulias, Sotirios A; Hartmann, Ola; Wolff, Max; Hjörvarsson, Björgvin
Abstract: We investigate the hysteresis obtained in the hydrogen absorption and desorption cycle for a single crystal P d / V 28 [ F e 4 / V 28 ] 11 superlattice. Below the critical temperature, a small but clear hysteresis is observed in the pressure-composition isotherms, while it is absent above. The experimental results thereby prove the relevance of macroscopic energy barriers for obtaining hysteresis in coherent structural transformations. The textured Pd layer exhibits substantially larger hysteresis effects, which can be related to an irreversible energy loss caused by defect generation in Pd.